Governing Religion: Colonial Legality, State, and the Case of Hijab in India - Thahir Jamal Kiliyamannil (Muslim Politics Review, 2025)
In March 2022, India’s Karnataka High Court ruled that the wearing of hijab by Muslim students was not an ‘essential religious practice’ under Islam. This raised a question of authority to interpret Islamic law, as the judges effectively decided what constitutes Islam legitimately and what does not. To trace the genealogy of these modes of governing religion, the paper examines three connected moments—the Karnataka hijab case, the Indian Constituent Assembly debates of 1946-1949, and the codification of Islamic law by the British colonial government—as instances in which the authority of the state emerges in judicial, constitutional, and colonial registers respectively. Across these sites, using genealogical method, this article shows how the state has continuously reorganized Islamic legal and ethical traditions into manageable forms, producing self-organizing Muslim subjects. I argue that the court’s capacity to define and limit Islamic norms is structurally embedded in the grammar of the modern state and its logic of governance, inherited and reconfigured from colonial techniques of defining and regulating religion.